Promoting organizational citizenship behaviour through high involvement human resource practices and organizational justice among hotel frontline employees in Malaysia : an attempt to reduce turnover intention / Wee Yu Ghee. - Wee, Yu Ghee (2010)
Acknowledging the need to pool human capital in the light of strong relational infrastructure so as to increase employees retention, this study examines the possibility of inducing organizational citizenship behaviour (OCB) through human resource (HR) philosophy embraced by the organizations, high involvement HR practices and organizational justice administered at the workplace. Two bases which form the relational infrastructure, namely leader-member exchange and trust in supervisor are posited to be potential mediators. Based on the social exchange theory, an integrated model with three sets of predicting variables (human resource philosophy, high involvement human resource practices and organization justice), two mediating variables (leader-member exchange and trust in supervisor), and two criterion variables (organizational citizenship behaviour and turnover intention), is presented in this study. Data was collected from frontline employees working in the five-star hotels in Malaysia and tested through structural equation modeling. Consistent with previous findings, HR philosophy drives the formulation of the bundles of high involvement human resource practices. A new contribution is added to the existing body of knowledge where such philosophy is found to have led to employees’ willingness in exhibiting citizenship behaviour directed at organizations (OCBO) as a whole. High involvement HR practices, however, do not elicit OCB but these practices are significantly related to leader-member exchange, another new theoretical insight which should invite future research. Except for distributive justice, procedural and interactional justice remain essential in promoting OCB but these relationships are mediated by subordinates’ trust in supervisor. Overall, the hotel frontline employees who have participated in this study exhibit more of citizenship behaviour that is directed to benefit organizations as a whole, rather than discretionary behaviour that is dedicated to specific individuals (OCBI). Significantly, OCBO is negatively related to employee’s turnover intention. Both theoretical and practical implications as well as avenues for future research are discussed.